2019
DOI: 10.1172/jci.insight.123611
|View full text |Cite
|
Sign up to set email alerts
|

Human PAH is characterized by a pattern of lipid-related insulin resistance

Abstract: IntroductionPulmonary arterial hypertension (PAH) is a life-limiting condition characterized by progressive vascular obliteration leading to right heart failure and ultimately death. Recent research has highlighted altered cellular and systemic metabolism as a key feature promoting pulmonary vascular disease and right heart BACKGROUND. Pulmonary arterial hypertension (PAH) is a deadly disease of the small pulmonary vasculature with an increased prevalence of insulin resistance (IR). Insulin regulates both gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 50 publications
9
86
1
Order By: Relevance
“…In a recent PAH plasma proteomics study, IGFBP2 was significantly increased compared to healthy controls [20]. In the current study, we measured IGFBP2 and total IGF1/2 levels in two independent PAH cohorts, as well as a healthy control cohort to evaluate the value of these proteins as diagnostic biomarkers for PAH; we then evaluated the relationships of these protein biomarkers with PAH progression and severity; finally, we evaluated IGFBP2 in the human PAH lung and pulmonary vascular cells.…”
Section: Introductionmentioning
confidence: 94%
“…In a recent PAH plasma proteomics study, IGFBP2 was significantly increased compared to healthy controls [20]. In the current study, we measured IGFBP2 and total IGF1/2 levels in two independent PAH cohorts, as well as a healthy control cohort to evaluate the value of these proteins as diagnostic biomarkers for PAH; we then evaluated the relationships of these protein biomarkers with PAH progression and severity; finally, we evaluated IGFBP2 in the human PAH lung and pulmonary vascular cells.…”
Section: Introductionmentioning
confidence: 94%
“…Given that PAH is associated with insulin resistance in other contexts [5][6][7][8], it is surprising that PAH patients exhibited increased insulin sensitivity and hepatic insulin extraction. Upon closer examination, however, other studies in PAH [7,18] have also found decreased insulin concentrations during oral glucose tolerance testing which indirectly suggests greater insulin sensitivity (calculated by HOMA-IR). Hepatic insulin extraction is typically reduced in individuals with impaired glucose tolerance, diabetes [19], and obesity [20], and contributes to the hyperinsulinaemia associated with these pathological states.…”
mentioning
confidence: 91%
“…This approach has the disadvantage of not allowing the discrete analysis of specific fatty acid substrates, which could be handled differently. However, the relevance of the substrates we analyzed is supported by the reported increase in circulating plasma concentrations of palmitic acid, oleic acid and lineolic acid by 12.0, 5.0 and 4.9-fold, respectively, in PAH versus control subjects 41 .…”
Section: Discussionmentioning
confidence: 86%
“…The pathologic phenotype of PH cells can be reversed, at least in part, by targeting the altered metabolism. Excessive proliferation and apoptosis resistance in PASMCs can be reversed by increasing glucose oxidation by treating the cells with DCA or blocking fatty acid oxidation such as with ranolazine, which increases glucose intake into the cells via the Randle cycle 5,41,42 . Our studies broaden these data, with the observation that even in the context of increased glycolysis induced by TGF-β in PASMCs, glucose remains a major source of carbons for the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%